2010
DOI: 10.1074/jbc.m110.118950
|View full text |Cite
|
Sign up to set email alerts
|

The Archaeal Lsm Protein Binds to Small RNAs

Abstract: Proteins of the Lsm family, including eukaryotic Sm proteins and bacterial Hfq, are key players in RNA metabolism. Little is known about the archaeal homologues of these proteins. Therefore, we characterized the Lsm protein from the haloarchaeon Haloferax volcanii using in vitro and in vivo approaches. H. volcanii encodes a single Lsm protein, which belongs to the Lsm1 subfamily. The lsm gene is co-transcribed and overlaps with the gene for the ribosomal protein L37e. Northern blot analysis shows that the lsm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(114 citation statements)
references
References 74 publications
6
101
0
7
Order By: Relevance
“…The diversity of biological activities of Lsm proteins compared to their more specialized Sm counterparts supports this two-step evolution model (Beggs, 2005;Khusial et al, 2005). The presence of up to three Lsm proteins in archaea, as well as an Hfq-like protein in archaeal M. jannaschii, further supports a common ancestor of eukaryotic and archaeal Lsm proteins (Fischer et al, 2011). A few multidomain proteins incorporating Lsm components have been observed (summarized, Figure 2).…”
Section: Phylogeny Of Lsm Protein Sequencessupporting
confidence: 57%
See 1 more Smart Citation
“…The diversity of biological activities of Lsm proteins compared to their more specialized Sm counterparts supports this two-step evolution model (Beggs, 2005;Khusial et al, 2005). The presence of up to three Lsm proteins in archaea, as well as an Hfq-like protein in archaeal M. jannaschii, further supports a common ancestor of eukaryotic and archaeal Lsm proteins (Fischer et al, 2011). A few multidomain proteins incorporating Lsm components have been observed (summarized, Figure 2).…”
Section: Phylogeny Of Lsm Protein Sequencessupporting
confidence: 57%
“…Hfq controls gene expression either by rearranging the RNA secondary structure, or by increasing the concentration of RNA locally to promote RNA-RNA interactions (Moll et al, 2003;Lease & Woodson, 2004;Afonyushkin et al, 2005). A similar mode of binding to sRNA was recently observed for the archaeal Lsm from Haloferax volcanii (Fischer et al, 2011). As for the eukaryotic Lsm proteins, Hfq is required for deadenylation-dependent mRNA decay.…”
Section: Specific Functions Of Bacterial Hfqmentioning
confidence: 55%
“…To date, very few of the newly reported candidate sRNAs in the archaea have been functionally characterized [2,13,37] Co-immuno-precipitation with the Lsm protein, the archaeal homolog of Hfq, was used to "capture" sRNAs in vitro [6]. However, the role of Lsm -or any other RNA-binding proteinremains to be elucidated in the archaea.…”
Section: Future Prospectsmentioning
confidence: 99%
“…sRNAs in bacteria and eukarya play essential roles in transcriptional regulation, chromosome replication, RNA processing and modification, mRNA stability and translation, and even protein degradation and translocation [3][4][5]. Recently, it was discovered that archaeal genomes encode for large numbers of sRNAs and that many of them are responsive to environmental stresses [1, 2,[6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In general they are very stable and sometimes the presence of chaotropic agent is necessary for their disruption. [31,35,36] We have previously reported that contribution of hydrophobic interactions, hydrogen bonds and salt bridges to the stability of Sm oligomers. [37] In order to better understand the nature of these assemblies, in this study we have analyzed the contribution of non-canonical interactions to the stability of assemblies.…”
Section: Introductionmentioning
confidence: 99%